Interrelation between neutrophil-lymphocyte ratio and chronic lower limb ischemia - O. M. Voloshyn (Zaporožskij Medicinskij Žurnal)
Purpose. The aim is to study the specifics of neutrophil - lymphocyte ratio (NLR) in patients with chronic lower extremity ischemia.